(untitled) (Journal of Foreign Language Studies, 2023)
In the context of globalisation, Vietnamese people have more and more opportunities to communicate in foreign languages. Thus, ‘standard’ pronunciation becomes an essential need of the learner, as well as an expectation from the teacher. In this study, we conduct a survey with all lecturers at the Department of Italian Studies (Hanoi University, Vietnam) on teaching Italian pronunciation to Vietnamese students at A1 level (complete beginners). We thence come up with suitable teaching methods along with some recommendations for better teaching quality. These include: applying communicative approach, performing pair/group work, using the course book, avoiding interference during students’ oral task and delaying mistake correction, and using cassette, CD or similar technical facilities.